MODELING OF LASER ENGRAVING OPERATION USING THE ROBODK SOFTWARE ENVIRONMENT AND A ROBOT MANIPULATOR - POLISHCHUK, ANDRII; HARBAR, YEVHEN; POLISHCHUK, OLEH; DUKA, OLEKSANDR; GIERGIEL, MARIUSZ (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article discusses the methodology for modeling and simulating the laser engraving process using the RoboDK software environment. The use of robotic systems in production processes allows you to increase the accuracy of material processing, reduce costs and minimize the likelihood of errors. One of the key aspects of implementing such technologies is preliminary digital testing, which allows you to optimize the parameters of the manipulator motion trajectories and check their effectiveness without the need for physical intervention in the equipment. As part of the study, an algorithm for creating a virtual environment in RoboDK was implemented, which includes importing CAD models, setting coordinate systems, calibrating the tool and building the optimal laser engraving trajectory. The use of modeling makes it possible to assess possible collisions, determine the permissible ranges of manipulator motion and adapt the laser beam parameters in accordance with the characteristics of the surface being processed. Testing of a robotic manipulator equipped with a laser head was implemented, which allowed assessing the stability of the system and compliance with the given trajectory. A comprehensive approach to the analysis of the kinematics of the manipulator movement was implemented, which includes a study of the influence of speed, acceleration and tilt angle on the accuracy of engraving. The simulation made it possible to determine the optimal operating modes of the laser system, as well as adjust the control parameters to minimize errors. The results obtained demonstrate the feasibility of using RoboDK for preliminary testing and debugging of laser engraving technological processes. The use of simulation allows you to significantly reduce the time for developing and setting up the production process, reduce the risk of errors and increase the quality of the final product. The proposed approach can be used to improve the control algorithms of robotic manipulators in other areas of production that require high accuracy and stability of operations.
Keywords: RoboDK; laser engraving; robotic system; modeling; simulation; robot manipulator; robotic arm